2021
DOI: 10.1590/1806-9304202100s200009
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and burden in mothers of children with congenital Zika syndrome during COVID-19 pandemic

Abstract: Objectives: to evaluate burden, frequency of anxiety and signs and symptoms of depression in mothers of children with congenital Zika syndrome (CZS) during the COVID-19 pandemic and the social isolation period. Methods: this is a cross-sectional study conducted with mothers who care for their children with CZS. The data were collected by an online form with questions regarding mother's socioeconomic conditions and questions related with Zarit burden scale and Beck's inventories on depression and anxiety. Spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
0
0
2
Order By: Relevance
“…Further, the suspension of health services and development support during the COVID‐19 pandemic led to remote care by health professionals and a rehabilitation routine for mothers and children, strengthening telemedicine. Mothers in this study expressed apprehension and insecurity about performing rehabilitation exercises at home without the direct supervision of physical therapists, similar to Gama et al 52 Some mothers reported that even with the guidance of physical therapists, the children did not show noticeable improvements. Vale et al 53 also identified regression in the development of children with CZS with exercises performed at home by mothers who learned them in therapy or were guided remotely.…”
Section: Discussionsupporting
confidence: 79%
“…Further, the suspension of health services and development support during the COVID‐19 pandemic led to remote care by health professionals and a rehabilitation routine for mothers and children, strengthening telemedicine. Mothers in this study expressed apprehension and insecurity about performing rehabilitation exercises at home without the direct supervision of physical therapists, similar to Gama et al 52 Some mothers reported that even with the guidance of physical therapists, the children did not show noticeable improvements. Vale et al 53 also identified regression in the development of children with CZS with exercises performed at home by mothers who learned them in therapy or were guided remotely.…”
Section: Discussionsupporting
confidence: 79%
“…Esse risco ainda é maior quando a criança apresenta problemas de comportamento (van Driessche et al, 2014). Outras condições de saúde, como o autismo (Faro et al, 2019) e síndrome congênita (Gama et al, 2021), também associam o estresse parental à sobrecarga de cuidados. Essa sobrecarga pode ser ainda maior na ausência de suporte social, tendo como consequência estratégias de ajustes mais pobres (Calderon & Greenberg, 1999).…”
Section: Discussionunclassified
“…Embora atualmente não ocorram altas taxas da doença, novos casos de microcefalia por Zika continuam sendo notificados no país. Com a pandemia pela COVID-19, as crianças vítimas da síndrome congênita pelo vírus Zika, citadas como grupo vulnerável, vivenciam um segundo surto viral potencialmente fatal (6,23) . Para muitas crianças, as terapias e consultas foram substituídas pela estadia prolongada em casa, pelo teleatendimento e por crises socioeconômicas.…”
Section: Discussionunclassified